ProBDNF and its receptors in immune-mediated inflammatory diseases: novel insights into the regulation of metabolism and mitochondria - Li, Qiao; Hu, Yue-Zi; Gao, Shan; Wang, Peng-Fei; Hu, Zhao-Lan; Dai, Ru-Ping (Frontiers in Immunology, 2023)
Immune-mediated inflammatory diseases (IMIDs) consist of a common and clinically diverse group of diseases. Despite remarkable progress in the past two decades, no remission is observed in a large number of patients, and no effective treatments have been developed to prevent organ and tissue damage. Brain-derived neurotrophic factor precursor (proBDNF) and receptors, such as p75 neurotrophin receptor (p75NTR) and sortilin, have been proposed to mediate intracellular metabolism and mitochondrial function to regulate the progression of several IMIDs. Here, the regulatory role of proBDNF and its receptors in seven typical IMIDs, including multiple sclerosis, rheumatoid arthritis, systemic lupus erythematosus, allergic asthma, type I diabetes, vasculitis, and inflammatory bowel diseases, was investigated.